STUDI KELAYAKAN EKONOMI PEMBANGUNAN UNDERPASS PADA SIMPANG JL. GATOT SUBROTO-JL. AHMAD YANI DI KOTA DENPASAR - Lina Sarasdevi Santosa; P. Alit Suthanaya; I B. Rai Adnyana (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2016)
Abstract : Based on data from the Central Statistics Agency (BPS) of Bali in 2013, the population density in the Metropolitan area SARBAGITA (Denpasar-Badung-Gianyar-Tabanan) was 1.057 inhabitants/km2 with an area of 1.753,63 km2 and population was 1.853.017 inhabitants. Availability of facilities and adequate transportation infrastructure is needed, but in fact the performance of roads in the city center has declined. It is characterized by an increase in travel delay problem. Traffic delay problems in the City of Denpasar commonly occur on the stretch of Gatot Subroto street. To minimize the existing problems, Denpasar City Government plans to develop an underpass at the intersection of Gatot Subroto street and Ahmad Yani street. The aim of this study was to analyze the direct benefits of underpass for road users, to analyze the costs necessary to realize and operate the underpass, and to analyze the economic feasibility of the underpass development investment. Based on primary data and secondary data were obtained from government agencies, the method of analysis in this study used the technique of Net Present Value (NPV), Benefit Cost Ratio (BCR) and Internal Rate of Return (IRR). Economic analysis conducted in this study used three criteria (NPV, BCR and IRR) with three interest rates (12%, 15% and 18% per year) stating that the construction of an underpass was economically feasible. For example in the second scenario where the interest rate 15% gain on the analysis of value NPV, BCR and IRR respectively is Rp. 233.462.340.102,00; 1,948 and 30,81%. Suggestions can be submitted from this research is the need to contemplate the effect of changes in land use in areas close to the area around the underpass and needed further study that takes into account the needs of additional traffic lanes.